(3GdebGHdI GdUMajI (B.. (3af (B:s (3Odjd Yedj ddUMaj (B/s - (3HjGLj, TjQdjs; (3YHO GdQDhas ((3GdbGgQI (B:s (3GdLeYjI GdeUQjI dfTQ GdeYQaI h GdKbGaI GdYGdejI ,s, 1991)
(3Gf af ELQGA GdebGHdI GdUMajI gh fhY ef GdHQGYI h GdegGQI h GdebOQI JJhaQ abW ef gDdGA Gd(B\(3jf jJeJYhf HGdehgHI GdUMajI h jecfc Gf JUHM UMajG GaVddh JLQj ebGHdGJ GcKQ JCKjQG Yf WQjb GdeYQaI h GdJLQHI h GdNHQI h gOG GdcJGH jbOe Gdjc NdGUI JLGQH GdYOjO ef cHGQ GdUMajjf aj GdGPGYI h aj GdJdjaRjhf h aj GdUMGaI Yf af GdebGHdI GdUMajI Gfge jYdehfc aj gPG GdcJGH cja JSLd GdedGMXGJ GKfGA GdebGHdI h cja JMUd Ydi GLGHGJ Yf GSFdJc GdUYHI h GNjQG cja JMQQ ehVhY GdebGHdI GdUMajI h HYO Gf JbQC gPG GdcJGH fSJWjY Gf JUHM GcKQ NHQI h egGQI aj af GLQGA GdebGHdGJ GdUMajIs
Keywords: (3GdUMGaIs; (3GdebGHdI GdUMajIs